Evaluation of triple hormonal content (ER, PR, and HER\2neu)of breast cancer specimens obtained from breast cancer patients using tru-cut biopsy - Jasim, Mustafa H.; Zaid Akool, Mohammed A.-; Al- Obaidi, Safa M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Breast cancer is the commonest type of malignancy among women worldwide and in Iraq. Tru-cut needle biopsy technique provides adequate tissue for histopathological diagnosis of suspected breast lumps and assessment of hormonal receptors (estrogen, progesterone and HER2neu) prior to surgical operation. Objectives: To assess estrogen, progesterone andHER2neu expression using breast cancer tissue specimens obtained by tru-cut biopsy, to correlate the findings with clinicopathological parameters of known prognostic significance in breast cancer patients. Patients and Methods: This prospective study was held within the Main Referral Center for Early Detection of Breast Tumors/Medical City Teaching Hospital and the Iraqi National Cancer Research Center/Baghdad University from May 2012 to the end of December 2012. Sixty-two females aged 25-73 years who presented with a breast lump were involved and examined using the triple assessment technique. A triple hormonal assessment (ER, PR & Her2) of the examined biopsies obtained by tru-cut needle for patients with suspected breast cancer was performed. The results were compared with the corresponding clinical and pathological parameters. Results: Data for excisional biopsy were available for 25 cases of the total number of women presented with breast lump. All of these cases showed similar histopathological results compared to Tru-cut biopsy results. Non-significant correlation was found between expression of ER, PR and HER2neu and the age of women, family history, and the site of the lump.On the other hand, a significant relationship was displayed between HER2neu over expression and the histopathological grading and age of the breast cancer patient. Conclusion: Tru-cut needle biopsy technique should be promoted nationwide in surgical departments to provide an insight to the type of mammary carcinoma, its aggressiveness, hormone receptor content and predict response to primary therapy before mastectomy.